Análise da Sustentabilidade de empreendimentos habitacionais vinculados a políticas públicas no período 2008-2010: aplicabilidade de requisitos Greenbuilding na construção civil de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The construction industry, which is responsible for the built environment we live in, is the human activity with the greatest impact on the environment, which is the reason why we can unequivocally infer that there is no sustainable human settlements without sustainable construction. Since Agenda 21 arrangements to facilitate relations between the concept of sustainable development and the construction sector are sought, with emphasis on the participation of the CIB (International Council for Research and Innovation in Building and Construction) and certification systems as creators of strategies and assessment mechanisms that are successful in many countries with so-called greenbuildings. They congregate practices of designing structures and the make use of environmentally responsible processes and efficient use of resources throughout the entire lifecycle of a building. They are also committed with the reduction of the overall impact of the built environment on human well-being and the natural environment by: efficient use of energy, water and materials; protection of occupant health and improvement of productivity and quality of life of workers; reduction of waste, pollution, environmental degradation, among others.The objective of this research was to evaluate the applicability of adopting greenbuilding requirements as a strategic orientation for constructions towards sustainability in the residential segment of Manaus, affected by housing policies. Therefore, a proposal for a site evaluation tool (PIAL) was constructed, based on the analysis of three certification systems: LEED (Leadership in Energy and Environmental Design), CSH (Code for Sustainable Home) and Selo Casa Azul. The PIAL was applied in two projects and the results showed the incipient stage of adoption of requirements for sustainable construction projects, with an average compliance of 31%. Moreover, the applicability of these requirements has also been studied, showing that more than 70% of the requirements were declared as being applicable. Taking into account that the requirements, mostly, are not adopted despite being applicable, a method of ranking, analytic hierarchy process (AHP) has been tested to support the creation of an Agenda for Sustainable Construction, which lists requirements in order priority and environmental management tools that will encourage its adoption in the current stage of construction in Manaus.
Keywords: Construção vicil; Desenvolvimento sustentável; Política habitacional; Greenbuilding; Sistemas de certificação; CIÊNCIAS AGRÁRIAS